Public-Private Relationship in Primary Care: preliminary considerations - Carneiro Junior, Nivaldo; Nascimento, Vânia Barbosa do; Costa, Ieda Maria Cabral (Saúde e Sociedade, 2011)
This paper aims to present some notes on the public-private relationship in the organization and provision of primary care services in the context of the current policies of Sistema Único de Saúde (SUS - Brazil's National Health System). The debate on the public-private relationship in health care emerged as a major issue in the context of the State reform movement from 1980 onwards, presenting views that challenge the government's role in providing social goods, and criticizing its efficiency in running public services. Thus, the nonprofit (non-governmental - NGO) organizations arise as the social agents that are suitable to play this role in partnership with public power/government. Traditionally, primary health care has been a direct responsibility of the government, but in the context of the reforms, proposals have been made to change this central governance, moving the task of running primary care services and facilities towards the private sector. In Brazil, this question emerged more forcefully at the beginning of the 1990s with the recruitment of professionals through partnerships between the public sector, charities and nonprofit organizations, enabling the implementation and expansion of the Family Health Strategy, particularly in large urban centers. The state of São Paulo has accumulated extensive experience in the articulation between public and private in health care, particularly in primary care, through social organizations. It is necessary to enhance the debate about the public-private relationship, especially in primary care, in order to recognize the possibilities and limits of actions by the non-governmental sector.